2018
DOI: 10.1186/s12903-018-0664-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral diseases and socio-demographic factors in adolescents living in Maasai population areas of Tanzania: a cross-sectional study

Abstract: BackgroundOral diseases may cause serious health problems, especially in socially disadvantaged populations and in low-income countries. In populations living in the rural areas of Tanzania there is paucity of reports on oral health. The study aim was to estimate the prevalence, severity and socio-demographic distribution of oral diseases/conditions in adolescents living in Maasai population areas of Tanzania and to compare oral diseases/conditions between Maasai and non-Maasai ethnic groups.MethodsA total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 64 publications
6
44
0
3
Order By: Relevance
“…All these exposed them to various risk factors of oral diseases and affected their psychological, social and quality aspects of their life .. Moreover, the present findings and also previous ones have shown that non-Maasai adolescents are more frequently affected by oral diseases than their Maasai counterparts [23]. Those from the least poor families were more likely to report oral impacts than those from the poorest families.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…All these exposed them to various risk factors of oral diseases and affected their psychological, social and quality aspects of their life .. Moreover, the present findings and also previous ones have shown that non-Maasai adolescents are more frequently affected by oral diseases than their Maasai counterparts [23]. Those from the least poor families were more likely to report oral impacts than those from the poorest families.…”
Section: Discussionsupporting
confidence: 77%
“…The estimated minimum sample size for this study, 845 adolescents was obtained by assuming a margin error of 5% and, confidence intervals of 95%. Details about the sampling technique have been described elsewhere [23]. Thus, in this study, we did a secondary analysis of a study planned for other purposes.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have assessed the prevalence of tooth decay both in populations that present high levels of fluorine and in others that present lower levels. [15][16][17][18][19][20][21][22][23] In 1994, a World Health Organization Expert Committee published a consensus report on the role of fluoride in the promotion of oral health all over the world. 44 Assessing the prevalence of caries in schoolchildren living in areas with different levels of fluoride, Sukhabogi et al observed the highest prevalence in the group in the low fluoride area, followed by the groups in the high and very high area.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] Numerous studies have attempted to correlate caries with dental fluorosis and have reported changes in the risk of decay depending on the degree of severity of the condition. [15][16][17][18][19][20][21][22][23] Fewer studies have explored the association between dental fluorosis with periodontitis. The role of some of the etiological factors of periodontal disease such as age, gender, ethnicity, socio-economic status, lifestyle, smoking and oral hygiene has been studied in some populations in India 24,25 but the effect of fluoride on periodontal tissue remains controversial, even though its association with tooth decay is well established.…”
Section: Introductionmentioning
confidence: 99%